Fermentation of Trichoderma for biological control using local inputs in Costa Rica - Becker, Patrick (2024)
Introduction. Supply chain issues have increased the costs of raw material and reduced the availability of materials for the production of biological control agents. This can result in greater disease pressure and lower yields on farms. Objective. To determine the effect of different amounts of starch and the use of local ingredients in small- and large-scale fermentation processes for Trichoderma harzianum. Materials and methods. The study was conducted in San José, Costa Rica, between 2016 and 2018. Flask experiments were performed to investigate the reduction or elimination of starch in commercial fermentation media. Fermentation vessel trials were conducted to evaluate the effectiveness of an alternative local medium, which included three treatments: 1) commercial medium as a control, 2) 10 % molasses medium, and 3) 10 % molasses with 0.5% yeast extract. Viable spore counts were performed to determine colony-forming units (CFU/mL). Results. Reducing starch to 10 % of the original medium had no impact on CFU/mL. However, the absence of starch resulted in uneven growth during fermentation. Molasses produced approximately half the CFU/mL compared to the commercial medium but exceeded the threshold of 107 CFU/mL used in studies for the biological control of plant pathogens. Results obtained in a commercial-scale fermenter were similar to those of pilot-scale fermentation. Conclusion. Reducing starch content in the commercial medium did not affect growth, but the absence of starch led to solid mycelium clumps. The use of a local molasses-based medium on a commercial scale feasible as long as the required viable spore count for field use is maintained.